Strategi Pengembangan Materi Layanan BK untuk Mendukung Implementasi Kurikulum Merdeka dalam Pelayanan Bimbingan Konseling (Studi Kasus di SMPIT Annida' Lubuklinggau) - Seprianto, Seprianto; Hartini, Hartini; Fadila, Fadila; Ristianti, Dina Hajja; Rizal, Syamsul (JOEAI (Journal of Education and Instruction), 2024)
Strategi Pengembangan Materi Layanan BK untuk Mendukung Implementasi Kurikulum Merdeka dalam Pelayanan Bimbingan Konseling (Studi kasus di SMPIT Annida' Lubuklinggau)The Independent Curriculum has become a primary focus in the development of the education system in Indonesia. Emphasizing the strengthening of creativity, innovation, and character aspects, the Independent Curriculum aims to prepare students to face global challenges. This research aims to identify and develop effective strategies for developing counseling services materials that support the implementation of the Independent Curriculum at SMPIT Annida' Lubuklinggau. The Independent Curriculum is the main focus in the development of the education system in Indonesia, with the goal of preparing students to face global challenges and shape a highly competent, independent, and competitive younger generation. This study uses a qualitative approach with a case study at SMPIT Annida' Lubuklinggau. The research results indicate that the strategy for developing counseling services materials at this school begins with initiation by school leaders, involving key stakeholders. The socialization process of the Independent Curriculum is carried out gradually, both within the school and to the general public through social media. The strategies implemented include the development of Higher-Order Thinking Skills (HOTS), strengthening character education, the preparation of a one-page Counseling Service Implementation Plan (RPL), and the enhancement of Information Computer and Technology (ICT) competence by counseling teachers. These strategies reflect the school's commitment to developing an inclusive and participatory approach to support the implementation of the Independent Curriculum. In conclusion, this research provides valuable contributions to addressing issues and challenges in counseling services, bridging the gap between the vision of the Independent Curriculum and day-to-day educational practices in the field. Effective and innovative development strategies for counseling services materials can be a crucial step in preparing the younger generation to face the increasingly complex and diverse demands of the future.